Construction and physical properties of heat-insulating water-dispersion paint coatings - Saienko, N.; Demidov, D.; Popov, Y.; Bikov, R. (Ways to Improve Construction Efficiency, 2019)
The article discusses the construction and physical properties of heat-insulating water-dispersion paint coatings. Test methods, carried out in accordance with international standards, investigated the possibility of using heat-insulating waterdispersion paint coatings as a protective and decorative finish of plastered building facades.